2021
DOI: 10.3389/fmed.2021.737713
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Profiles of Patients With Antipsychotic-Related Constipation Treated With Electroacupuncture

Abstract: Antipsychotic-related constipation (APRC) is one of the most common side effects of taking antipsychotic medication. APRC can seriously impact patient quality of life and is potentially fatal, though the efficacy of current APRC treatments is low for most patients. In this study, we conducted a controlled, pilot randomized, sham-electroacupuncture (SEA) study to assess the efficacy of electroacupuncture (EA) in patients with APRC. We used 16S rRNA gene sequencing to assess the microbial profiles of these patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 83 publications
(109 reference statements)
0
11
0
Order By: Relevance
“…The effect of GM on Parabacteroides was greater than that on GMOS. Parabacteroides have the ability to metabolize carbohydrates and produce SCFAs [35], and have beneficial effects on metabolic disorders [36,37]. However, it is debatable whether Parabacteroides are beneficial or pathogenic.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of GM on Parabacteroides was greater than that on GMOS. Parabacteroides have the ability to metabolize carbohydrates and produce SCFAs [35], and have beneficial effects on metabolic disorders [36,37]. However, it is debatable whether Parabacteroides are beneficial or pathogenic.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture, as one of the TCM therapy methods, has been found to modulate the composition of intestinal flora in the progression of treating some diseases. [164][165][166]. Although there were few clinical trials exploring the mechanism of acupuncture in the management of diabetes from the perspective of intestinal flora, animal tests have manifested electroacupuncture was beneficial in increasing the diversity of gut flora and promoting colonic motility, which may be used to explain its hypoglycemic mechanism.…”
Section: Acupuncture Therapymentioning
confidence: 99%
“…As described previously, some evidence in animal models of acupuncture on obesity and modulation of gut microbiota composition is presented. In humans, the evidence is still scarce but emerging changes in species abundance and diversity of the gut microbiome have been documented in patients undergoing treatment with EA ( 49 , 53 , 198 ). In perimenopausal women with abdominal obesity, EA for eight weeks in combination with diet decreased the abundance of the species and increased the species diversity of gut microbiota ( 49 ).…”
Section: Acupuncture Clinical Human Studiesmentioning
confidence: 99%
“…A recent sham-controlled study in adults with antipsychotic-related constipation treated with EA showed that richness of various bacterial strains such as Klebsiella and Gammaproteobacteria was significantly higher after acupuncture, and was associated with significantly increased spontaneous bowel movements and reduced use of rescue medication. Moreover, Firmicutes-to-Bacteroidetes ratio was increased post-treatment ( 198 ). In a population of patients with knee osteoarthritis, eight weeks of EA modified gut microbiota diversity and microbiota richness of species ( 53 ).…”
Section: Acupuncture Clinical Human Studiesmentioning
confidence: 99%